Parent Attitudes Toward Pain Management for Childhood Immunizations. Issue 8 (August 2016) - Connelly, Mark; Wallace, Dustin P.; Williams, Kristi; Parker, JoLynn; Schurman, Jennifer V.
Abstract : Objectives: Evidence-based pain-limiting strategies for pediatric immunizations remain underutilized, with barriers identified to date mostly pertaining to health care providers and systems of care. The present study sought to quantify and investigate parent attitudes toward pain management as another potential barrier to the routine use of pain-mitigating strategies during immunizations. Materials and Methods: Questionnaires measuring parent attitudes, willingness to pay, and perceived barriers for using pain management for immunizations were completed by 259 parent/guardians of children ages 0 to 5 years attending appointments at an urban primary care clinic in the Midwestern United States. Results: Parent attitudes toward pain management for immunization were relatively normally distributed and varied from strongly positive to negative, with 33% of parents disagreeing that they were concerned about the pain their child may experience and 50% agreeing that there are no lasting negative effects from immunization pain. Negative parent attitudes were associated with willingness to spend less in money or time for pain management and with greater perceived significance of cost, time, and other barriers for using pain-mitigating strategies. Discussion: Some parents perceive limited value in trying to reduce pain during immunizations such that they may be hesitant to invest much time or effort in interventions. Greater success of translating evidence-based pain management into practice therefore may require accounting for differences in parent attitudes by tailoring educational efforts and pain management options accordingly.